Respuesta :

I suppose the claim is [tex]5 \mid 6^n - 1[/tex] for [tex]n\in\Bbb N[/tex].

When [tex]n=1[/tex], we have [tex]6^1 - 1 = 6 - 1 = 5[/tex], and of course 5 divides 5.

Assume the claim holds for [tex]n=k[/tex], that [tex]5 \mid 6^k - 1[/tex]. We want to use this to show it holds for [tex]n=k+1[/tex], that [tex]5 \mid 6^{k+1} - 1[/tex].

We have

[tex]6^{k+1} - 1 = \left(6^{k+1} - 6\right) + \left(6 - 1) = 6\left(6^k - 1\right) + 5[/tex]

Since [tex]5 \mid 6^k - 1[/tex], we can write [tex]6^k - 1 = 5\ell[/tex] for some integer [tex]\ell[/tex]. Then

[tex]6^{k+1} - 1 = 6\cdot5\ell + 5 = 5(6\ell + 1)[/tex]

which is clearly divisible by 5. QED

ACCESS MORE